2008
DOI: 10.1348/135910706x171469
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the relationship between psychological distress and recurrence of upper respiratory tract infections in chronic fatigue syndrome

Abstract: CFS patients reported more frequent URTIs than healthy controls and these recurrences were preceded by high levels of psychological stress. High levels of stress were also associated with greater subsequent fatigue. Possible explanations of these results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The hypothesis that patterns of immune activity associated with MDD should have decreased mortality from infection in ancestral environments appears to face a challenge from data indicating that depression worsens outcome in a number of infectious processes 253, 254, 255, 256, 257, 258, 259, 260 and is associated with impairments in adaptive immune mechanisms important for protection against both viruses and bacteria. 13, 261, 262 To address this challenge, we have first to inquire whether innate immune inflammatory processes that are increased in MDD produce the patterns of infectious vulnerability and adaptive immune impairment that are apparent in depression.…”
Section: Patterns Of Immune Activation In Mdd and Protection From Infmentioning
confidence: 99%
“…The hypothesis that patterns of immune activity associated with MDD should have decreased mortality from infection in ancestral environments appears to face a challenge from data indicating that depression worsens outcome in a number of infectious processes 253, 254, 255, 256, 257, 258, 259, 260 and is associated with impairments in adaptive immune mechanisms important for protection against both viruses and bacteria. 13, 261, 262 To address this challenge, we have first to inquire whether innate immune inflammatory processes that are increased in MDD produce the patterns of infectious vulnerability and adaptive immune impairment that are apparent in depression.…”
Section: Patterns Of Immune Activation In Mdd and Protection From Infmentioning
confidence: 99%
“…A secondary aim was to compare the frequencies of health conditions and symptoms between the two groups. It was clear that the characteristic symptoms of CFS (Loblay et al, 2002;Faulkner and Smith, 2008) occurred in large percentages of the diagnosed participants, irrespective of their age and time since diagnosis. However, given that the CFS group displayed haemoglobin and erythrocyte concentrations within the respective normal ranges, it was unexpected to find a high percentage of the CFS group with either a previous or current diagnosis of iron deficiency/anaemia, and with elevated RDW and MCV.…”
Section: Discussionmentioning
confidence: 99%
“…The CFS group had a significantly lowertotal lymphocyte concentration and a lower CD4 + lymphocyte count, which may have clinical significance in terms of the ability of CFS patients to respond to infections (Lorusso et al, 2009).A high percentage of our CFS group reported recurring sore throats, indicative of upper respiratory tract infection (URTI). Recurring sore throats and inflamed lymph nodes are common symptoms of both CFS and URTI, and there is considerable evidence that CFS patients suffer from significantly more recurring episodes of URTI and other infectious illnesses compared to healthy controls (Loblay et al, 2002;Faulkner and Smith 2008). We reason that a lower CD4 + cell count might indicate an impaired Thelper lymphocyte response, as these cells produce interleukin-2 when activated and are integral to lymphocyte sub-set activation and proliferation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having coping resources (optimism and social support) predicted less relapses (Lutgendorf et al, 1995). In a diary study of CFS patients, Faulkner and Smith (2008) found that daily ratings of psychological distress predicted greater physical fatigue during the following week. Together, these findings suggest that emotional distress reactions (to environmental challenges and daily life stress) may trigger physical symptoms in CFS.…”
Section: Introductionmentioning
confidence: 99%